2016
DOI: 10.1080/00918369.2016.1191232
|View full text |Cite
|
Sign up to set email alerts
|

Same-Sex Couples’ Decisions and Experiences of Marriage in the Context of Minority Stress: Interviews From a Population-Based Longitudinal Study

Abstract: In the emerging context of marriage equality, it is important to explore the reasons for and experience of marriage for long-term same-sex couples, including the role of minority stress. In Wave 3 of the population-based, longitudinal CUPPLES Study we interviewed 21 long-term same-sex couples (14 female, 7 male) who resided in 12 different states and who were legally married. Couple members ranged in age from 37 to 84 and reported being together as a couple from 15 to 41 years. Seven couples lived in states th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 37 publications
1
33
0
1
Order By: Relevance
“…This aligns with findings of LGB individuals reporting more sexuality-specific support from friends than family (Doty, Willoughby, Lindahl, & Malik, 2010). In summary, our findings support similar experiences of increased recognition following marriage (Rostosky, Riggle, Rothman, & Balsam, 2016), as well as marriage prompting expressions of homonegativity by family and friends (Eskridge & Spedale, 2006;Lannutti, 2008). Taken together, the findings appear to support the argument that a lack of social support is a unique minority stressor for same-sex couples (Kurdek, 2005;Meyer, 2003), which appears to linger even despite access to marriage.…”
Section: Discussionsupporting
confidence: 90%
“…This aligns with findings of LGB individuals reporting more sexuality-specific support from friends than family (Doty, Willoughby, Lindahl, & Malik, 2010). In summary, our findings support similar experiences of increased recognition following marriage (Rostosky, Riggle, Rothman, & Balsam, 2016), as well as marriage prompting expressions of homonegativity by family and friends (Eskridge & Spedale, 2006;Lannutti, 2008). Taken together, the findings appear to support the argument that a lack of social support is a unique minority stressor for same-sex couples (Kurdek, 2005;Meyer, 2003), which appears to linger even despite access to marriage.…”
Section: Discussionsupporting
confidence: 90%
“…It is often used in combination with gender, feminist, or intersectional approaches and is emerging as highly applicable for the study of LGBTQ families (Farr, Tasker, & Goldberg, 2017; van Eeden‐Moorefield et al, ). For example, Rostosky, Riggle, Rothblum, and Balsam () applied minority stress theory to investigate long‐term same‐sex couples' decisions about and experiences of pursuing legal marriage. Prendergast and MacPhee () combined minority stress theory and intersectionality theory to analyze healthy family functioning in same‐sex parent families to focus on resilience.…”
Section: Situating the Critical Theoretical Terrain Of Gender Feminimentioning
confidence: 99%
“…Booker et al [ 6 ] demonstrated that these strategies were effective in longitudinal cohort studies that used the traditional data collection methods of postal surveys, face-to-face visits (home or on-site), and telephone interviews or surveys. However, these cohort retention strategies may not be as well suited to contemporary methods of collecting longitudinal data, such as web and mobile surveys [ 9 ], wearable sensors (e.g., FitBits) [ 10 ], short message services (SMS) [ 11 ], and groupware systems (e.g., video conferencing) [ 12 ]. Novel methods of engaging participants such as web advertising [ 13 ], social media [ 14 ], and electronic reminders [ 15 ], are also now being employed in cohort studies using both traditional and modern longitudinal data collection methods.…”
Section: Introductionmentioning
confidence: 99%